Alternative fluorophores designed for advanced molecular imaging. Issue 1 (January 2018) - Freidus, Lara G.; Pradeep, Priyamvada; Kumar, Pradeep; Choonara, Yahya E.; Pillay, Viness
Graphical abstract: Highlights: Alternative and novel fluorophores are required for advanced microscopy techniques. NIR fluorophores used to reduce signal to background ratios and improves penetration depths. Smart fluorophores have been designed to detect and image single molecules. Fluorophores possessing aggregation induced fluorescence can avoid fluorescent quenching. Abstract : Fluorescent molecular imaging has advanced drastically over the past decade. With the development of high-resolution microscopy techniques and the ability to visualize intracellular molecular events, there is a growing need for new fluorophores to accompany these fast-developing techniques. Therefore, there has been substantial development of alternative fluorophores for single-molecule detection and molecular imaging. These rationally designed fluorophores have infinite possibilities and novel fluorophores are constantly being produced for different applications. This review focuses on the recent developments in novel fluorophores designed for molecular imaging and single-molecule detection. Here, single-molecule imaging, smart fluorescent probes, two-photon microscopy, Förster resonance energy transfer (FRET) and super-resolution microscopy are discussed in detail. Teaser: A wide variety of alternative and novel fluorophores have been developed with wide-reaching applications in the fields of single molecule detection and molecular imaging.